Pola Adaptasi Masyarakat Terhadap Banjir Pasang Surut (ROB) di Kecamatan Penjaringan, Kota Jakarta Utara - Rafa Elysia Leandra; Saptono Putro (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Tidal flooding increasingly affects low-lying coastal areas in North Jakarta, particularly Penjaringan District, where recurrent inundation disrupts settlements, infrastructure, and livelihoods. This study analyzes the spatial distribution of tidal flood-prone areas, identifies key factors influencing community adaptation, and examines prevailing adaptation patterns. Employing a descriptive quantitative approach integrated with spatial analysis, primary data were gathered through field observations, structured interviews, and questionnaire surveys in Pluit and Penjaringan subdistricts, supplemented by secondary data for mapping and hazard assessment. Descriptive analysis evaluated internal factors like socio-economic characteristics, residence duration, and risk awareness, alongside external factors such as environmental conditions and infrastructure. Highest flood exposure in low-elevation, high-density areas near the coast. Communities adapt via physical, economic strategies for livelihood continuity, and social responses like collective action. These enhance short-term resilience but face constraints from limited resources and environmental pressures. Community-based adaptation reduces vulnerability, yet requires stronger integration with spatial planning and coastal policies for sustainable risk reduction.